Pelatihan Pembelajaran Tematik Terpadu dan Penilaian Autentik Kompetensi Abad 21 bagi Guru SDN Srengseng Sawah 12 Pagi - Nur Wahyuni; Mimin Ninawati; Sri Lestari Handayani (Jurnal Pengabdian Pada Masyarakat, 2021)
INTEGRATED THEMATIC LEARNING TRAINING AND AUTHENTIC ASSESSMENT OF 21ST CENTURY COMPETENCIES FOR TEACHERS OF SDN SRENGSENG SAWAH 12 PAGI. Integrated Thematic Learning is an approach in learning that intentionally links several aspects both within intra subjects and between subjects. With this integration, students will gain full knowledge and skills so that learning becomes meaningful for students. The meaning of Integrated Thematic learning is a learning approach that involves several subjects to provide meaningful experiences to students. Identification of partner problems, namely: (1) Teachers lack knowledge in implementing variations of learning approaches and learning models, (2) Lack of teacher understanding related to integrated thematic approaches, and (3) Lack of teacher understanding related to authentic assessment based 21st Century competence. The training activities were carried out in four sessions. Some of the material activities held at this training include: (a) Understanding and Reinforcement of Pedagogical Competence and Teacher Professionalism, (b) Understanding Integrated Thematic Learning,(c) Understanding of Evaluation of Learning Implementation Plans and Learning Assessment, and (d) Understanding of the Authentic Assessment of 21st Century Competence. Participants in this activity were attended by 16 teachers at SDN Srengseng Sawah 12 Pagi. Through the training that has been done, the teachers of Srengseng Sawah 12 Pagi Elementary School can better understand and be motivated to carry out integrated thematic approaches and authentic assessments correctly in the School.